When Winners Feel Like Losers : Evidence from an Energy Subsidy Reform - Calvo-Gonzalez, Oscar; Cunha, Barbara; Trezzi, Riccardo (World Bank, Washington, DC, 2015)
In 2011 the Government of El Salvador implemented a reform to the gas subsidy that increased the welfare of households in all but the top two deciles of the income distribution. However, the reform turned out to be rather unpopular, especially among winners. This paper relies on ad hoc household surveys conducted before the implementation and in the following two and a half years to test which factors help explain the puzzle. The analysis uses probit and logit models to show that misinformation (a negativity bias by which people with limited information inferred negative consequences), mistrust of the government’s ability to implement the policy, and political priors explain most of the (un)satisfaction before implementation. Perceptions improved gradually—and significantly so—over time when the subsidy reception induced households to update their initial priors, although political biases remained significant throughout the entire period. The results suggest several implications with respect to policy reforms in cases where agents have limited information.